2006
DOI: 10.1109/twc.2006.1633366
|View full text |Cite
|
Sign up to set email alerts
|

Optimal call admission control with QoS guarantee in a voice/data integrated cellular network

Abstract: Abstmet-This paper addresses the issue of call admission control with the necesary QaS guarantee for a micddala integrated wireless cellular network. Specifically, we propose a new call admission control policy called Dual-Threshold Call Admission Conml (DT-CAC) policy. It uses hw rhresholdr, one to reserve channels for narrow-band voice handoffcalls, and the other for wideband data handoff Irffic. Its unique features am: 1) it adopts the Complete Sharing (CS) approach that maximizes the channel emciency; 2) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 21 publications
0
8
0
2
Order By: Relevance
“…However, they did not investigate how many channels should be increased or decreased to satisfy different QoS requirements of diverse call classes. Chau et al extended the LFGC scheme to incorporate the multiple traffic classes in [20]. Simulated annealing technique is employed to obtain the optimal control parameters.…”
Section: Related Work On Admission Control and Bandwidth Allocationmentioning
confidence: 99%
“…However, they did not investigate how many channels should be increased or decreased to satisfy different QoS requirements of diverse call classes. Chau et al extended the LFGC scheme to incorporate the multiple traffic classes in [20]. Simulated annealing technique is employed to obtain the optimal control parameters.…”
Section: Related Work On Admission Control and Bandwidth Allocationmentioning
confidence: 99%
“…Admission control is critical for supporting QoS when there are too many users that want to access the network simultaneously. In traditional cellular networks, many results have shown that the optimal admission control policy has a threshold structure (e.g., [6]- [8]). In cognitive radio networks, researchers have studied admission control for both underlay networks (e.g., [9]- [11]) and overlay networks (e.g., [12], [13]).…”
Section: Introductionmentioning
confidence: 99%
“…Predictive schemes suffer either from approximation of number of handoff arrivals in a cell as normal [1] or Poisson [2] distribution or from complex tracking of the mobility of users [3]. On the other hand, in static schemes [4], [5], the numbers of different classes of calls in a cell are considered for accepting a new call in that cell. In static schemes, a cell is studied to approximate the whole cellular network and these schemes suffer from the approximation of handoff arrival process as Poisson process for exponentially distributed call holding duration and cell residence time.…”
Section: Introductionmentioning
confidence: 99%